Management of Extrapulmonary Nontuberculous Mycobacterial Infections - Kasperbauer, Shannon; Huitt, Gwen (Seminars in Respiratory and Critical Care Medicine, 2013)
Nontuberculous mycobacteria represent a vast group of environmental organisms that have the potential to cause disease in humans. Unlike tuberculosis, these organisms are not known to be transmitted from human to human. The most common clinical presentation is pulmonary disease. Approximately 10% of infections manifest as extrapulmonary disease. The portals of entry are the respiratory tract, gastrointestinal tract, or direct inoculation via trauma or an invasive procedure. Like tuberculosis, the nontuberculous mycobacteria have the potential to infect any organ system given the opportunity in an immunocompromised host. The spectrum of disease is extensive ranging from self-limited furunculosis to life-threatening disseminated infection. Common extrapulmonary manifestations include lymphadenitis, disseminated disease, skin, soft tissue, and bone infection. Less common manifestations include keratitis, catheter-related bloodstream infections, septic arthritis, central nervous system infection, and peritonitis. The incidence of extrapulmonary infections is unknown. Outbreaks have been reported due to inadequate disinfection of surgical equipment or contamination of injected solutions or medications. A high index of suspicion is required when patients present with subacute or chronic complaints of extrapulmonary infection. This review addresses the management of the common extrapulmonary nontuberculous infections.
Keywords: nontuberculous mycobacteria; extrapulmonary infection; disseminated infection